2009
DOI: 10.5004/dwt.2009.729
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phenol and dye from aqueous solution using chemically modified date pits activated carbons

Abstract: ab s t r ac tThe adsorption of phenol and methylene blue (MB) on modified activated carbons has been investigated. The activated carbon was prepared from date pits by physical activation (CO 2 as activating agent). Oxidation in the liquid phase with nitric acid and thermal treatment under flowing nitrogen were carried out in order to produce samples with different surface chemical properties but with no major differences in their textural properties. The surface area and porosity were characterized by N 2 adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, low adsorption capacities or removal efficiencies of heavy metal ions are the main problem of these adsorbents. Therefore, research for finding new and more effective materials to be used as adsorbents is very important subject [10][11][12][13][14].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…However, low adsorption capacities or removal efficiencies of heavy metal ions are the main problem of these adsorbents. Therefore, research for finding new and more effective materials to be used as adsorbents is very important subject [10][11][12][13][14].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…(2014) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] www.deswater.com doi: 10.1080/19443994.2014.979237 therefore, identification of low-cost adsorbents would be greatly beneficial to the community as a whole. A number of studies have been reported in the literature in which low-cost adsorbents such as fly ash [15], rice husk char [16], pyrolyzed sewage sludge [17], lignite [18], Sargassum muticum [19], spent oil shale [20], bentonite [21], natural clay [22], wheat bran [23], and clay algae [24] were used as an alternative to activated carbon.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Over the years, adsorption has been considered to be one of the efficient methods [4,5] among various physico-chemical methods [6][7][8][9] available for the removal of phenol from aqueous effluents. Conventional adsorbents such as activated carbon [10][11][12][13][14] …”
Section: Introductionmentioning
confidence: 99%
“…Phenol and other aromatic compounds are ubiquitous contaminants in water [9][10][11][12]. The studies on sono-198 A.H. Mahvi, A. Maleki / Desalination and Water Treatment 20 (2010) 197-202 chemical degradation of phenol and substituted phenols have been reported [2,7].…”
Section: Introductionmentioning
confidence: 97%